2005
DOI: 10.1081/ja-200030662
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Self-Administered Alcoholism Screening Test (SAAST-R): A Pilot Study

Abstract: The original Self-Administered Alcoholism Screening Test (SAAST; Swenson and Morse, 1975) is a self-report alcoholism screening measure intended for use with adult medical patients. However, the SAAST does not indicate the recency of alcohol use-related problems, not all items use the appropriate verb tense for assessing lifetime experience of alcohol use-related problems, many of the items contain out-dated language, and the diagnostic criteria for alcohol dependence and alcohol abuse are not fully represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Results also indicated that the factor structure was similar for both the SAAST and SAAST‐R 1 . Factor analysis of the SAAST‐R items yielded a two‐factor solution accounting for 81% of the variance.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Results also indicated that the factor structure was similar for both the SAAST and SAAST‐R 1 . Factor analysis of the SAAST‐R items yielded a two‐factor solution accounting for 81% of the variance.…”
Section: Introductionmentioning
confidence: 77%
“…After 30 years of SAAST use among medical patients, however, several research and clinical issues pointed to the need for a revision 1 . The format and items of the SAAST were revised to allow for an improved clarity of the results, such as to allow the researcher or clinician to differentiate between current and past drinking status and to separate respondents in recovery from those with current dependence.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations